Nomenklatur Penataan Desa Adat Dalam Permendagri No. 1 Tahun 2017 Tentang Penataan Desa - LAINSAMPUTTY, NATANEL (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2022)
The purpose of this paper is to examine the arrangement of traditional villages in Indonesia, which in its development nomenclature must be used in accordance with the Minister of Home Affairs Regulation No. 1 of 2017 concerning Village Arrangement is to use the nomenclature of changing the status of the village to become a traditional village. the basis for consideration is that the status of the community called customary community units still has the status of a village. The research method used in this research is a normative research method with an approach to legislation and literature study, theory and legal principles.